Characterizing and improving the sensory and hedonic responses to polyphenol-rich aronia berry juice. (1st December 2016) - Duffy, Valerie B.; Rawal, Shristi; Park, Jeeha; Brand, Mark H.; Sharafi, Mastaneh; Bolling, Bradley W.
Abstract: Interest in nutrient-rich berry juices is growing, but their high polyphenol levels render them sensorily unappealing. Fifty adults, who were assessed for sensory phenotype and dietary behaviors, provided sensory and palatability ratings of juices from 'Viking' aronia berries for each of seven harvest weeks. By peak harvest, juice preference increased two-fold, averaging neither like/dislike. This hedonic shift was associated with: increases in juice sugars paralleling increases in perceived sweetness (maximum = weak); reductions in percent acidity paralleling reductions in sourness (minimum = moderate), astringency (minimum = to just above weak) and bitterness (minimum = just below weak). About 25% of adults liked the aronia juice, including adults who also liked an aqueous citric acid solution (average rating = moderately sour) or those who reported adventurous eating behaviors. Bitter taste phenotype, measured by propylthiouracil or quinine bitterness, failed to explain significant variation in juice sensation or preference. We also collected sensory and preference ratings from juice collected at peak harvest blended with sugar and/or sweet olfactory flavoring (10 ppm ethyl butyrate). Increasing juice sweetness by adding 5% sucrose decreased sourness and improved preference from weak dislike to weak like. Adding sweet olfactory flavoring decreased juice sourness without changing preference. Adding sweet flavoring and 3% sucrose resulted in reduction of sourness and improvements in preference ratings comparable to 5% added sucrose. Neither added sugar nor flavoring blocked juice astringency. In summary, these findings suggest that aronia juice, even from berries picked at peak harvest, appealed to only a few adults (sour likers or adventurous eaters). Although enhanced sweetness, with added sugar and sweet olfactory flavoring, improved aronia juice preference, broader sensory approaches are required to blunt astringency for greater consumer appeal.